(untitled) (Journal of Global Accounting, 2022)
The objective of this study was to ascertain the effect of Corporate Social Responsibility Costs on Financial Performance of Deposit Money Banks listed on Nigeria Stock Exchange for a ten year period ranging from 2011- 2020. Thirteen (13) Deposit Money Banks were purposively selected from a population of Fourteen (14) listed Deposit Money Banks. The proxies for Corporate Social Responsibility Costs were Corporate Donations, Occupational Health and Safety Cost, Training Cost and Remediation Cost while Return on Assets was employed as Financial Performance index. Four (4) hypotheses were formulated. Ex-Post facto research design was adopted while Pearson Correlation Coefficient and Panel Least Square (PLS) Regression analysis via STATA 13 statistical software were used to test the hypotheses of the study. The result of this study showed that Corporate Donations, Occupational Health and Safety Cost, Training Cost and Remediation Cost have a significant positive effect on Return on Assets at 5% level of significance respectively. Based on the empirical findings, this study suggests that Deposit Money Banks should involve in more CSR activities to increase their financial performance since CSR practices have a positive effect on financial performance of the deposit money banks in Nigeria.